PENINGKATAN TINGGI BADAN Z SCORE TB/U PADA BALITA STUNTING DENGAN PEMBERIAN ZINC - Utami, Rina; Setianto, Rony; Dewi, Belinda Arbitya; Maftukhin, Achmad (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
The incidence of stunting in Indonesia is ranked 5th in the world. One of the focuses of the Indonesian government is the problem of stunting children, the standard for assessing the nutritional status of children with measurement results is a threshold (z-score) <-2 SD to -3 SD. Stunting that is not matched by catch-up growth can result in decreased growth, stunting is a health problem in society because it can increase the risk of morbidity, death and mental and motor difficulties.The impact of stunting is the development of decreased cognitive function. The Indonesian government is trying to address and reduce the prevalence of stunting in every region, especially villages that are prioritized for stunting. Improved nutrition is aimed at the first 1000 days of life group. One way to handle stunting cases is by giving zinc because of the impact if toddlers are deficient in zinc, namely growth can fail and tissue volume can decrease (loss of issue). Methods: this study used an experimental design with a randomized pretest posttest design, the number of respondents was 15 stunting toddlers who were given zinc supplements for 6 months. In this study, there were differences in height and Z score for height/age before and after being given zinc supplements with the results of p=0.000 and p=0.004. Zinc supplementation can have an effect on increasing height and Z scores in stunting toddlers.